1998
DOI: 10.1007/s004200050310
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and incidence of hand dermatitis in hairdressing apprentices: results of the POSH study

Abstract: Objective: Occupational skin changes in hairdressers are very common. Morbidity, however, has not yet been quanti®ed precisely. Methods: A cohort of 2,352 hairdressing apprentices (of the 2,570 invited to participate, i.e., 91.5% response) was prospectively followed for the duration of their vocational training (3 years) by three examinations. Three waves (years) were recruited in 1992, 1993, and 1994 from 15 vocational training schools in northwestern Germany. Results: The point prevalence of (mostly slight) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
96
2
6

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(111 citation statements)
references
References 7 publications
7
96
2
6
Order By: Relevance
“…In the healthcare workers the attributable risk was even higher and amounted to 37.4% 59) . ASD was also closely related to the development of skin problems during vocational training in hairdressing 66,67) , nursing 63) and food industry apprentices 68) , but not in trainee metal workers 56) . Loffler et al 69) showed that the risk of atopic health care employees (assessed by Diepgen score) to develop skin changes was especially high in the first 18 months of their training.…”
Section: Atopic Diathesis and Icdmentioning
confidence: 99%
See 1 more Smart Citation
“…In the healthcare workers the attributable risk was even higher and amounted to 37.4% 59) . ASD was also closely related to the development of skin problems during vocational training in hairdressing 66,67) , nursing 63) and food industry apprentices 68) , but not in trainee metal workers 56) . Loffler et al 69) showed that the risk of atopic health care employees (assessed by Diepgen score) to develop skin changes was especially high in the first 18 months of their training.…”
Section: Atopic Diathesis and Icdmentioning
confidence: 99%
“…In hairdressers, atopic status showed to increase the risk of leaving the profession by up to 20% 66,73) .…”
Section: Atopic Diathesis and Icdmentioning
confidence: 99%
“…Inflamed and damaged skin is at greater risk of sensitization. Atopic individuals are also more likely to leave the hairdressing profession than nonatopic ones, perhaps because the former have a greater susceptibility to irritants 13) . The International Agency for Research on Cancer (IARC) recently reasserted that the substances to which hairdressers and barbers are exposed in the workplace are probably carcinogenic, although there is generally only limited evidence for their carcinogenicity 1) .…”
mentioning
confidence: 99%
“…Frizeri su prepoznati kao zanimanje koje uključuje značajne zdravstvene rizike, ponajviše za kožu (1,2). Rizik od kožnih bolesti u frizera vezan je uz svakodnevnu izloženost brojnim čimbenicima s nadražujućim i senzibilizirajućim djelovanjem na kožu.…”
unclassified
“…Brojni kemijski sastojci boja za kosu, izbjeljivača, kemikalija za trajno kovrčanje, ali i šampona i preparata za njegu kose, senzibilizirajuće djeluju na kožu izazivajući pojavu alergijskog kontaktnog dermatitisa. Kao najčešći profesionalni frizerski alergeni pri tom se spominju parafenilendiamin, amonijev persulfat i gliceril monotioglikolat (1)(2)(3). Jednom nastala profesionalna kožna bolest u frizera vrlo često ima nepovoljnu prognozu i dovodi do značajnoga gubitka kvalitete života i radne produktivnosti (4), a često i do profesionalne nesposobnosti za rad, tj.…”
unclassified